Understanding Low-income Older Adults' Intention to Consume Fruits and Vegetables. Issue 2 (4th March 2021) - Jung, Seung Eun; Shin, Yeon Ho; Im, Jinyoung; Hermann, Janice; Ellis, Amy; Crowe-White, Kristi
ABSTRACT: The purpose of this study was to identify determinants of low-income older adults' intention to consume fruits and vegetables (F&V) using the model of goal-directed behavior. A sample of 400 low-income community-dwelling older adults participated in this cross-sectional study. Data were analyzed using Structural Equation Modeling. Results from this study indicated that subjective norm, perceived behavioral control, and positive anticipated emotion were significant predictors of desire. Desire was a significant predictor of intention and past behavior had a significant direct effect on intention. Results of this study can inform future intervention programs aimed to increase F&V intake among low-income older adults.